ASSESSMENT OF THE POTENTIAL FOR REUSING TREATED DOMESTIC WASTEWATER FOR URBAN AGRICULTURE IN TAN UYEN CITY, BINH DUONG PROVINCE - Huynh The An; Ho Bich Lien; Nguyen Duc Dat Duc; Dao Minh Trung (HUIT Journal of Science, 2025)
In the context of rapid urbanization and increasing water demand in agriculture, the reuse of treated domestic wastewater is emerging as an important solution toward developing green and sustainable cities. This study aims to assess the potential for reusing treated domestic wastewater in Tan Uyen City, Binh Duong Province. Data were collected from the city’s domestic wastewater treatment system, with key analyzed parameters including BOD5, COD, TSS, NH4+, NO3-, total nitrogen (TN), total phosphorus (TP), alkalinity, and color. The results indicate high treatment efficiency, with COD reduced by 94.49% (from 290.4 ± 0.2 mg/L to 16 ± 1 mg/L), BOD5 by 97.1% (from 93.36 ± 0.03 mg/L to 2.706 ± 0.001 mg/L), TSS by 97.36% (from 196.8 ± 0.1 mg/L to 5.2 ± 0.1 mg/L), and Coliform by 99.69% (from 80162 ± 3 MNP/100 mL to 250.6 ± 0.1 MNP/100 mL). Additionally, NH4+ decreased from 40.54 ± 0.02 mg/L to 0.168 ± 0.02 mg/L (99.59% efficiency), NO3- from 4.58 ± 0.01 mg/L to 1.34 ± 0.03 mg/L (70.74%), total nitrogen from 39.6 ± 0.1 mg/L to 6.96 ± 0.01 mg/L (82.42%), and total phosphorus from 3.84 ± 0.01 mg/L to 1.14 ± 0.01 mg/L (70.31%). The color was significantly reduced from 427.4 ± 0.1 Pt/Co to 20.8 ± 0.1 Pt/Co (95.13%). The analysis results show that the treated water meets the requirements of QCVN 39:2011/BTNMT, and it can be reused for purposes such as irrigation of landscape greenery, vegetables, or short-term industrial crops. The study recommends enhancing post-treatment water quality monitoring and developing effective reuse models to improve water resource conservation, reduce pressure on freshwater sources, and promote sustainable urban agricultural development in Tan Uyen City.